Design and Finite Element Analysis of Brake Disc Heat Dissipation Rib for Urban Rail Transit Vehicle - WU Na; SONG Hao; YANG Jianwei; WU Chunguang; WANG Chengxu (Chengshi guidao jiaotong yanjiu)
[Objective] At present, the heat dissipation performance of brake discs for urban rail transit vehicles needs to be improved. Therefore, it is necessary to study the optimization design scheme for a new type of heat dissipation ribs. [Method] By adopting the numerical simulation method of finite element analysis, a three-dimensional brake disc model with new type heat dissipation ribs is established through computer-aided design software. Different design schemes for heat dissipation ribs are proposed, and the thermal analysis simulation for these schemes is conducted by the finite element analysis technology. In terms of heat conduction efficiency and heat dissipation paths on axle-mounted brake discs and on wheel-mounted ones, different heat dissipation rib designs are compared, and the heat dissipation capacities of the brake discs with different heat dissipation ribs are evaluated. [Result & Conclusion] Both the design schemes of the wheel-mounted straight-plate heat dissipation ribs and the axle-mounted cylindrical heat dissipation ribs significantly optimize the heat dissipation paths, improving the transfer efficiency of heat from the heat source to the external cooling medium. The cyclic symmetric design of the heat dissipation ribs effectively reduces the complexity of the brake disc production process, and minimizes damages simultaneously to the relevant components such as the axles, therefore can provide a guarantee for the safe and reliable train operation.